Campylobacter jejuni outer membrane vesicle‐associated proteolytic activity promotes bacterial invasion by mediating cleavage of intestinal epithelial cell E‐cadherin and occludin. (10th November 2015) - Elmi, Abdi; Nasher, Fauzy; Jagatia, Heena; Gundogdu, Ozan; Bajaj‐Elliott, Mona; Wren, Brendan; Dorrell, Nick
Summary: Outer membrane vesicles (OMVs) play an important role in the pathogenicity of Gram‐negative bacteria. Campylobacter jejuni produces OMVs that trigger IL‐8, IL‐6, hBD‐3 and TNF‐α responses from T84 intestinal epithelial cells and are cytotoxic to Caco‐2 IECs and Galleria mellonella larvae. Proteomic analysis of 11168H OMVs identified the presence of three proteases, HtrA, Cj0511 and Cj1365c. In this study, 11168H OMVs were shown to possess proteolytic activity that was reduced by pretreatment with specific serine protease inhibitors. OMVs isolated from 11168H htrA, Cj0511 or Cj1365c mutants possess significantly reduced proteolytic activity. 11168H OMVs are able to cleave both E‐cadherin and occludin, but this cleavage is reduced with OMVs pretreated with serine protease inhibitors and also with OMVs isolated from htrA or Cj1365c mutants. Co‐incubation of T84 monolayers with 11168H OMVs results in a visible reduction in both E‐cadherin and occludin. The addition of 11168H OMVs to the co‐culture of live 11168H bacteria with T84 cells results in enhanced levels of bacterial adhesion and invasion in a time‐dependent and dose‐dependent manner. Further investigation of the cleavage of host cell structural proteins by C. jejuni OMVs should enhance our understanding of the interactions of this important pathogen with intestinal epithelial cells.